Development of a Short Form of the Elemental Psychopathy Assessment. (December 2013) - Lynam, Donald R.; Sherman, Emily D.; Samuel, Douglas; Miller, Joshua D.; Few, Lauren R.; Widiger, Thomas A.
The Elemental Psychopathy Assessment (EPA) is a 178-item self-report measure designed to assess the basic elements of psychopathy from a Five-Factor Model perspective: Anger, Arrogance, Callousness, Coldness, Disobliged, Distrust, Dominance, Impersistence, Invulnerable, Manipulation, Opposition, Rashness, Self-Assurance, Self-Centered, Self-Contentment, Thrill-Seeking, Unconcern, and Urgency. The present article reports on the development of a short-form version of the EPA in two large undergraduate samples using item response theory. The validity of the resultant, 72-item, item response theory–derived short form is compared against the validity for the full scale in the undergraduate samples and smaller forensic sample. Results indicate that the 18 subscales of the EPA short form remain relatively reliable, possess an internal structure virtually identical to the full version, and manifest highly similar correlational profiles to a variety of criterion measures. The EPA short form is offered as a viable assessment of psychopathy when assessment time is limited. Implications of these findings are discussed.